Using Information Practices of Nurses to Reform Information Literacy Instruction in Baccalaureate Nursing Programs - Diekema, Anne R.; Hopkins, Elizabeth (Betsy) S.; Patterson, Brandon; Schvaneveldt, Nena (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2019)
Objective - Seeking information is a key element of evidence based practice and successful healthcare delivery. Significant literature exists on both the information seeking behaviour of professional nurses and information literacy teaching methods, but scarce evidence connects nurses’ information behaviour and environments with their education. This study sought to use data from nursing alumni to answer the following research questions: What are the current information practices of professional bachelor’s-prepared nurses? How do recently-graduated nurses suggest that their education could have better prepared them to find and evaluate information in the workplace?Methods - The researchers conducted a descriptive study using a 59-item survey instrument with a variety of question formats including short-answer, multiple choice, Likert, and open response. The researchers distributed the survey to baccalaureate nursing alumni who graduated in 2012-2017 from four universities in the state of Utah in the United States.Results - Nurses seek practical information primarily to provide informed patient care, while also clarifying medical situations and expanding their health care knowledge. They frequently consult nursing colleagues and physicians when seeking information. The majority of nurses consult electronic health records daily. Respondents described time as the biggest barrier to accessing information. They requested authentic, clinically-focused scenarios, training on freely-accessible resources, and more explicit teaching of lifelong learning skills, such as critical thinking.Conclusion - Information literacy education should prepare student nurses for the fast-paced information environment they will face in the workplace. This means incorporating more patient-focused scenarios, freely available quality resources, and time-based activities in their education. The researchers suggest areas to prepare nurses for information seeking, including problem-based clinical scenarios, building guides with databases accessible for free or little cost, and added emphasis on critical thinking and self-motivated learning.